Pengembangan Kemampuan Pemecahan Masalah Peserta Didik Melalui Problem Based Learning Pada Pendidikan Agama Islam - Kianda, alka; Azwar, Beni; Iswanto, Rahmat (Universitas Majalengka, 2024)
This study aims to analyze the development of students' problem-solving skills through Problem-Based Learning (PBL) in the subject of Islamic Religious Education (PAI) in the Independent Curriculum of SMA Negeri 04 Kepahiang. The research uses a qualitative method with an exploratory case study approach. Data were obtained through interviews, observations, and documentation, and then analyzed in a qualitative descriptive manner. The results of the study show that the application of PBL with relevant socio-moral cases is able to improve students' critical thinking skills and understanding of religious concepts. Teacher support through feedback is effective in connecting theory and practice. Obstacles such as teacher resistance and time constraints can be overcome with teacher training and school management support. This study recommends strengthening PBL to improve the quality of PAI learning.